A Cloud-based Distributed Data Collection System for Decentralised Wastewater Treatment Plants. (2015) - O'Donovan, P.; Coburn, D.; Jones, E.; Hannon, L.; Glavin, M.; Mullins, D.; Clifford, E.
Abstract: Compliance with increasingly stringent legislation is one of the key challenges in the wastewater technology sector in the European Union (EU). Many EU countries have chosen to use decentralised wastewater treatment plants (WWTPs) because of reduced infrastructural requirements. However, achieving compliance of regulatory standards using a decentralised strategy can be difficult and costly due to inefficient operating cost-efficiency, infrequent monitoring capability, as well as the logistical challenges faced by operators travelling between sites. With these problems in mind, this paper presents a distributed information system that was developed as part of an Irish-based research project that was funded by Enterprise Ireland. The system focuses on the acquisition and hosting of data from decentralised WWTP's to facilitate reliable and timely access to data that can be used for monitoring and analysis, without incurring the inherent logistical and technical costs associated with manual data collection methods.